Sustainable Energy Business Model and Strategies for Marketing of Clean Energy Products in Rural Areas of India. Issue 1 (1st October 2022) - Das, Shiv Sankar; Nayak, Bijaya Bijeta; Behera, Debashree Debadatta; Sahu, Rita Kumari; Sahu, Sasmita; Giri, Soumya Ranjan
Abstract: Our world's problem can be resolved with the use of energy. Energy is the fundamental structure for economic development of any area, state, or a country. In today's world, energy access is a relevant issue. Availability of energy is required to improve health, agricultural productivity, and educational outcomes. The increased need for energy has led to a reliance on large-scale fossil fuel extraction and use. As a result, environmental degradation, pollution, and ecological imbalance have occurred. In order to find a solution, clean energy is vital. As a result, focusing on the shift from conventional to clean energy sources is critical. "Clean energy" is obtained mostly from non-polluting, zero-emission sources, as well as energy conserved via efficiency improvements. Access to clean energy can aid in the development of rural tribal communities. This paper focuses on a case analysis where sustainable energy business model was devised. The paper is divided into three segments. The first segment focuses on the introduction to clean energy, clean technology and clean energy products. Second segment focuses on the sustainable energy business model in rural areas of South Odisha, where a Digital Business Centre (DBC) was established. Finally the third segment focuses on the strategies for marketing of clean energy products and an Entrepreneurial-cum-SHG Model. Methodology/design/approach: In this study, a descriptive case technique was employed, and instances were purposefully chosen. Data was gathered to better comprehend the theoretical ideas of actors, factors, and their relationships, as well as to create the conceptual framework. The framework's applicability was tested using an action research approach (partial intervention in the ecosystem). Findings: Variety of players and variables were identified, and their relationships were established. Originality/value- An innovative strategy to clean energy intervention for income generation was established and a sense of entrepreneurial attitude was also developed.